Utilization of Leaf Turi (Sesbania grandiflora) Fermentation In Artificial Feeds on Growth Fish Seed Baung (Hemibagrus nemurus) - Puspita Dewi; Adelina '; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted on 1 April-26 May 2015. The purpose of this study to determine the number of leaves turi fermented flour in fish feed formulation baung (Hemibagrus nemurus) the effect on growth, feed efficiency and protein retention. This study uses a completely randomized design (RAL) with one factor, 5 treatments and 3 replications. Treatments using turi leaves fermentation where are P1 (0%), P2 (5%), P3 (10%), P4 (15%) and P5 (20%). Which Feed protein contain 35%. The results showed that the highest treatment contained in P3. Use turi leaves fermented formulated in the feed as much as 10%, produces the best baung fish seed growth is digestibility of the feed 30.07%, the feed efficiency is 24.46%, protein retention is 10.98% and specific growth rate is 2.02%.Key word: (Hemibagrus nemurus), Fermentation Leaf Turi